Voltaire and the 1760s - Cronk, N (Voltaire Foundation, 2017)
The 1760s was a pivotal decade for the philosophes. In the late 1750s their cause had been at a low ebb, but it was transformed in the eyes of public opinion by such events as the Calas affair in the early 1760s. By the end of the decade, the philosophes were dominant in key literary institutions such as the Comédie-Française and the Académie française, and their enlightened programme became more widely accepted. Many of the essays in this volume focus on Voltaire, revealing him as a writer of fiction and polemic who, during this period, became increasingly interested in questions of justice and jurisprudence. Other essays examine the literary activities of Voltaire’s contemporaries, including Jean-Jacques Rousseau, Chamfort, Rétif, Sedaine and Marmontel. It is no exaggeration to describe the 1760s as Voltaire’s decade. It is he more than any other author who set the agenda and held the public’s attention during this seminal period for the development of Enlightenment ideas and values. Voltaire’s dominance of the 1760s can be summed up in a single phrase: it is in these years that he became the ‘patriarch of Ferney’. Peter France, John Renwick: a tribute Publications of John Renwick Nicholas Cronk, Voltaire and the 1760s: the rule of the patriarch I. Voltaire’s contemporaries Jean Ehrard, Tempête dans un gobelet: esquisse de mémoire en défense de M. Ozy, apothicaire auvergnat du dix-huitième siècle David Adams, Illustration and interpretation: the frontispiece to Marmontel’s Bélisaire Michael Cardy, Some references to English writers in Marmontel’s Poétique française (1763) Katherine Astbury, The success of Marmontel’s moral tales on the French stage 1760-1770 David McCallam, Physiocrats and barbarians: moral economies in Chamfort’s comedies John Dunkley, Sedaine’s Maillard: the gauntlet, the calque and the seneschal’s revenge Cecil Courtney, Constant d’Hermenches: correspondent of Voltaire and Belle de Zuylen Christopher Todd, Glimpses of France and the French (1760-1769) in three English provincial newspapers David Coward, ‘Je deviens auteur’: Restif in the 1760s Graham Gargett, Caveirac, Protestants and the presence of Voltairean discourse in late-eighteenth-century France Katharine Swarbrick, Voltaire, Rousseau and the uses of frivolity II. Voltaire James Hanrahan, Creating the ‘cri public’: Voltaire and public opinion in the early 1760s Russell Goulbourne, Voltaire and the Calas affair in England Christiane Mervaud, Voltaire et le Beccaria de Grenoble: Michel-Joseph-Antoine Servan Olivier Ferret, Les stratégies éditoriales des Mélanges voltairiens Nicholas Cronk, Le Philosophe ignorant, volume de mélanges Simon Davies, Le Pyrrhonisme de l’histoire, Voltaire’s anthology of contes Richard Francis, The Ingénu’s children Jonathan Mallinson, Les Lettres d’Amabed: rewriting Graffigny’s Lettres d’une Péruvienne? Adrienne Mason, Unheard voices: two English translations of Voltaire’s L’Ingénu David Williams, Voltaire and Thomas Otway Haydn Mason, Voltaire, directeur de conscience: his correspondence with Mme Du Deffand Peter France, Last words Index